2017
DOI: 10.11648/j.bs.20170305.12
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Strategy in Cancer Chemotherapy, Aimed Not at Killing Cancer Cells, but the Recovery of Their DNA, Modified by Active Oxygen

Abstract: Abstract:It is considered that the cause of some forms of cancer is the modification of DNA by active oxygen. This suggests that the removal of oxygen from the composition of such DNA will cure these forms of cancer. For the practical implementation of this idea proposed a number of substances that are harmless to humans, but have the ability to penetrate into cell nuclei and bind active oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…It was previously established that the fluorescence spectra of aqueous solutions containing various sources of atomic hydrogen have peaks with maxima at wavelengths that well coincide with the lines of the Ballmer series [14,15]. For example, such a peak is clearly visible on the fluorescence spectrum of an aqueous solution of formic acid containing zinc oxide ( Figure 6) -it is known that zinc oxide catalyzes the decomposition of formic acid into two hydrogen atoms and a carbon dioxide molecule [3]:…”
Section: Atomic Hydrogen Fluorescence In Aqueous Media As a Promisingmentioning
confidence: 98%
“…It was previously established that the fluorescence spectra of aqueous solutions containing various sources of atomic hydrogen have peaks with maxima at wavelengths that well coincide with the lines of the Ballmer series [14,15]. For example, such a peak is clearly visible on the fluorescence spectrum of an aqueous solution of formic acid containing zinc oxide ( Figure 6) -it is known that zinc oxide catalyzes the decomposition of formic acid into two hydrogen atoms and a carbon dioxide molecule [3]:…”
Section: Atomic Hydrogen Fluorescence In Aqueous Media As a Promisingmentioning
confidence: 98%
“…Thus, these types of cancer therapies combine the killing of cancer cells with the simultaneous stimulation of new cancer cells and tumor growth, which is counterproductive. It is also counterproductive to use photosensitizes for additional oxidation of the DNA of cancer cells [42][43][44] , that is, for the oxidation of those DNA that are already oxidized [21,31,[36][37][38][39][40].…”
Section: Figure 10 So the Tumor Is Irradiated With A Red Lasermentioning
confidence: 99%
“…Based on this, it should be noted that anticancer therapy is more preferable, aimed not at destroying cancer cells, but at their deep chemical recovery [40] . At the same time, negative electrification of cancerous tumors creates conditions for the emergence of new nerve contacts (Figure 3), which means for the restoration of the innervation of damaged tissues, in the absence of which the tissues swell at least uncontrollably.…”
Section: Figure 10 So the Tumor Is Irradiated With A Red Lasermentioning
confidence: 99%
“…Previously obtained results suggested that gaseous hydrogen can fluoresce in aqueous media, forming peaks at wavelengths that correspond to Ballmer series lines [15]. Testing the ability of atomic hydrogen to fluoresce in aqueous media consisted in the study of the fluorescence of water that came in contact with various sources of atomic hydrogen.…”
Section: Shifts In the Spectra Of Laser-induced Fluorescence Of Moistmentioning
confidence: 99%